What Is Backward Disequilibrium and How Do I Treat it?. Issue 2 (April 2015) - Scheets, Patricia L.; Sahrmann, Shirley A.; Norton, Barbara J.; Stith, Jennifer S.; Crowner, Beth E.
<x xml:space="preserve">Abstract</x> Background and Purpose: Postural vertical refers to a component of an individual's perception of verticality that is derived from information about the direction of gravitational forces. Backward disequilibrium (BD) is a postural disorder observed in some older adults who have a distortion in their perception of postural vertical. Individuals with BD sustain their center of mass (COM) posterior to their base of support and resist correction of COM alignment. The purposes of this case study are to describe a patient with BD and propose a physical therapy management program for this condition. Case Description and Intervention: The patient was an 83-year-old woman admitted for home care services 4 months after falling and sustaining a displaced right femoral neck fracture and subsequent hemiarthroplasty. Details of the clinical examination, diagnosis, and intervention are provided and a treatment protocol for physical therapy management is suggested. Outcomes: During the episode of care, the patient (1) decreased her dependence on caregivers, (2) surpassed minimal detectable change or minimal clinically important improvements in gait speed and on the Short Physical Performance Battery and Performance-Oriented Mobility Assessment, and (3) achieved her primary goal of staying in her own apartment at an assisted living facility. Discussion: Knowledge of BD coupled with a thorough clinical examination may assist physical therapists in identifying this condition and employing the specific intervention we have proposed. We believe that failure to recognize and manage our patient's condition appropriately would have led to nursing home placement. Video Abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A94).